Comparison between Specificity and Sensitivity of Intestinal Giardialamblia Assays in AL-Door District, Salahdin Province, Iraq - Sinai Najy Muhsin AL-doury, (University of Thi-Qar Journal of Science, 2020)
The Giardia lamblia is known as a considerable cause of diarrhea in human. Difficulties are confronted in the detection of that parasite in patients’ faces because of intermittent excretion of the parasite.In this study it was determined specificity and sensitivity of floatation methodby zinc sulphate solution and ELISA assay for Giardialamblia detection compared with direct iodine stain methodAmong 82 patients who were attending AL-Door hospital through period of September to December 2018. The prevalence of Giardiasis was 32.9% and 67.1% was negative. As well this study showed that the percentage of G. lamblia infection was 31.7% by direct iodine stain method, 29.3% was by floatation methodand the sensitivity ratio was 92.3%, specificity was 100%,While 32.9% was positive by ELISA assay and the sensitivity ratio was 92.3%, specificity was 94.6%. Also our study found that the prevalence for Giardiasis depending on gender in this study was 67% for male, 33.3% for female. The results of study were showed the prevalence of infection was 23.2% in age group 8-25 years, 7.3% in 26-35 years and 2.4% in age group 36-45 years. The distribution of infection depends on residencewhich was 20.7% for rural and 12.2% for urban.